Mn3O4 based materials for electrochemical supercapacitors: Basic principles, charge storage mechanism, progress, and perspectives. (10th December 2022) - Beknalkar, S.A.; Teli, A.M.; Bhat, T.S.; Pawar, K.K.; Patil, S.S.; Harale, N.S.; Shin, J.C.; Patil, P.S.
Highlights: Basic properties of Mn3 O4 concerned with charge storage mechanism are discussed. Vivid work carried out on pristine Mn3 O4 and its limitations are put forth. Several strategies adopted to overcome limitations of pristine Mn3 O4 are focused. Remarks on scientific points and perspectives for further development are stated. Abstract: The captivating properties of supercapacitors (SCs) such as high power and reasonably high energy densities made them stand up as a versatile solution to emerging energy storage applications. Thus, everyone is in pursuit of improvisation of the energy storage characteristics of SCs. Hausmannite or manganese oxide (Mn3 O4 ) is a widely studied electrode material considering its fascinating features such as high theoretical capacitance (1370 F/g), variable oxidization states, prominent Jahn-Teller effect, broad potential window, environmentally benign and cost-effectiveness. A lot of research has been carried out on this material to unfold and improve its electrochemical aspects. In this review, comprehensive knowledge and innovative attempts taken to improve its energy storage of Mn3 O4 material are discussed. Firstly, the basic properties concerned with electrochemical charge storage such as valance states, crystal structure, band diagram and energy storage mechanism are discussed, followed by putting forth the limitations of Mn3 O4 . Later on, various strategies adopted to improve the electrochemical attributes of Mn3 O4 such as making composite with carbon-based materials, metal-based materials, polymers or doping metal atoms are thorough. Finally, remarks on key scientific points and perspectives for further development of energy storage in Mn3 O4 conclude this review. Graphical abstract: Image, graphical abstract